Contraindications to lumbar puncture as defined by computed cranial tomography. Issue 8 (August 1987) - Gower, D J; Baker, A L; Bell, W O; Ball, M R
Abstract : Papilloedema is not always an adequate predictor of potential complications from lumbar puncture, and many clinicians are using computed tomography (CT) before lumbar puncture in an effort to identify more accurately the "at risk" patient. This paper identifies the following anatomical criteria defined by CT scanning that correlate with unequal pressures between intracranial compartments and predispose a patient to herniation following decompression of the spinal compartment: lateral shift of midline structures, loss of the suprachiasmatic and basilar cisterns, obliteration of the fourth ventricle, or obliteration of the superior cerebellar and quadrigeminal plate cisterns with sparing of the ambient cisterns. These criteria should be considered to be contraindications to lumbar puncture.